16α-Hydroxyfriedelin and 3-Oxo-16-methylfriedel-16-ene as Building Blocks: Crystal Structure and Hirshfeld Surfaces Decoding Intermolecular Contacts. (24th October 2013) - Corrêa, Rodrigo S.; Duarte, Lucienir P.; Silva, Grácia D. F.; de Oliveira, Djalma M.; Ellena, Javier; Doriguetto, Antônio C.
Abstract : In this paper the importance of C–H ⋯ O intermolecular hydrogen bonds and van der Waals forces in crystal packing stabilization of 16 α -hydroxyfriedelin (1 ) and 3-oxo-16-methylfriedel-16-ene (2 ) is described. Compound1 is a natural product isolated from the hexane extract of Salacia elliptica branches, whereas compound2 is obtained from compound1 after dehydration accompanied by methyl migration of C-17 to C-16. The single-crystal X-ray diffraction experiments for1 and2 were carried out at 150 K, and the crystallographic study demonstrated that these compounds crystallize in noncentrosymmetric space groups, with1 showing an orthorhombic P21 21 21 space group and2 a monoclinic P21 one. Compounds1 and2 are composed of five fused six-membered rings presenting a chair conformation, except for the central ring of2, which adopts a half-chair conformation. In addition, the intra- and intermolecular parameters were studied using CCDC MOGUL analyses and Hirshfeld surfaces.